Penerapan Adab Penggunaan Media Sosial Siswa Sekolah Dasar: Komparasi Sekolah Islam dan Sekolah Umum - Ayu Kurnia; Dian Veronika Sakti Kaloeti (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2019)
This study aims to explore the implementation of Islamic values (adab) in using social media, also the differences between two different school cultures (Islamic school and public school). This qualitative research used case study method with focus group discussion on 20 teachers (5 teachers in every schools) and 10 primary students who actively used social media (5 Islamic school students and 5 public school students). This study identified two main Islamic values in social media behavior. First, the values of respecting others and speaking politely. Second, the rule to forbid students bring cell phones. Further, Islamic school parents and teachers more responsive to the students’ social media interaction rather than parents and teachers in public school. The schools seem to have strong regulation about social media use. However, the role of the parents on their children will determine the basic foundation of their ethics on social media use.